PROSPECTS OF ORGANIZING RENTAL OPERATIONS IN NON-GOVERNMENT EDUCATIONAL ORGANIZATIONS ON THE BASIS OF INTERNATIONAL STANDARDS OF FINANCIAL REPORTING - Aybek Nazarbaevich Abdullaev; Inomjon To‘raevich Jumaniyazov; Shavkat Bayramovich Babaev; Mirza Qilichbayevich Sabirov (Galaxy International Interdisciplinary Research Journal, 2024)
The reforms carried out by our state and government are aimed not only at pre-school and general high school education, but also in the direction of opening branches of private higher education institutions and prestigious higher education institutions of developed foreign countries, which will enable the formation of a healthy competitive environment in the higher education system, and the establishment of joint educational programs with them, is appearing. The types of activities related to the social sphere carried out in our country, in particular, the benefits created for legal entities engaged in the provision of non-state educational services, the correct organization of their tax relations as a legal entity, current tax benefits and their relative classification, conditions and procedures for using benefits, benefits In our opinion, the formation of skills in the correct use of the accounting reporting procedure and the current regulatory and legal documents related to this field is one of the most urgent issues today. Some of the provided benefits have their own characteristics in terms of duration, and some in relation to the type of activity. In this process, the correct use of tax benefits, their correct reflection in accounting is important, of course.